2017
DOI: 10.1111/jvp.12401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of cefazolin and ceftriaxone on canine chondrocyte culture

Abstract: Cephalosporins (CEFs) are antibiotics frequently used to treat bone infections and septic arthritis. The effects of CEFs on chondrocytes have not been studied until now. Cefazolin (cef1) and ceftriaxone (cef3), first-and third-generation CEFs, were selected to investigate their direct effects on normal and osteoarthritic (OA) primary canine chondrocytes, which were either nonstimulated or stimulated with the pro-inflammatory cytokine IL-1β. In our results, treatment with CEFs increased the negative effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…From the four included studies on the cephalosporin class, cefazolin doses ranging from 0.39 to 50 mg/mL demonstrated dose-dependent chondrotoxicity. 20,26,28 Ceftazidime in doses ranging from 0.39 to 25 mg/mL also demonstrated dose-dependent chondrotoxicity. 20,26 Although Gunal et al 29 did not find ceftriaxone to be chondrotoxic in a leporine model, they did not report a dosage used.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…From the four included studies on the cephalosporin class, cefazolin doses ranging from 0.39 to 50 mg/mL demonstrated dose-dependent chondrotoxicity. 20,26,28 Ceftazidime in doses ranging from 0.39 to 25 mg/mL also demonstrated dose-dependent chondrotoxicity. 20,26 Although Gunal et al 29 did not find ceftriaxone to be chondrotoxic in a leporine model, they did not report a dosage used.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, ceftriaxone at 4.17 -50 mg/mL in a canine model did demonstrate dose-dependent chondrotoxicity. 28 Aminoglycosides. Four out of the eight aminoglycoside studies assessed amikacin, which demonstrated dose-dependent chondrotoxicity in canine and equine models.…”
Section: Intra-articular Antibiotics Continuedmentioning
confidence: 99%
“…Sonuçlarımız, bakterisit olarak etkin doz olan 100 µg/ml'nin oldukça üzerinde kalan 250 µg/ml ve 500 µg/ml doz aralığında dahi sefazolin kullanımının, fibroblast hücrelerinin çoğalma hızı üzerinde negatif bir etkisi olmadığını ortaya koymaktadır. (18). Çalışmamızda ayrıca sefazolinin 500 µg/ml olarak uygulandığı gruplarda oksidatif stresi az da olsa arttırdığı gözlemlense de bu artış istatistiksel olarak anlamlı değildi ve literatürde bu verimizi destekleyecek başka bir yayına da rastlamadık.…”
Section: Sefazolin 3t3 Fare Fibroblastlarının Migrasyon Hızını Yavaşl...unclassified
“…Several drugs, such as local anesthetic drugs (10 mg/mL of lidocaine or 7.5 mg/mL of ropivacaine in human chondrocyte culture), corticosteroids (25 mm of dextramethasone, 25 mg/mL of prednisolone or 7 mg/mL of betamethasone in human chondrocyte culture), cefazolin (2.0-3.33 mg/mL in canine chondrocyte culture) and fluoroquinolones (182 mg/mL of enrofloxacin or 295 mg/mL of marbofloxacin), have been shown to produce adverse effects on articular cartilage including apoptosis and the inhibition of growth of chondrocyte cells (Chrysis et al, 2005;Farkas et al, 2010;Nakazawa et al, 2002;Siengdee et al, 2016;Siengdee et al, 2017). This phenomenon can result in a loss of extra-cellular matrix formation and the progressive degradation of articular cartilage (Farkas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can result in a loss of extra-cellular matrix formation and the progressive degradation of articular cartilage (Farkas et al, 2010). For example, antibiotics such as cefazolin (2.0-3.33 mg/mL) may cause apoptosis and necrosis of chondrocytes by inducing the alpha tumor necrosis factor (TNF-a) and matrix metelloproteinase (MMP) production, decreasing the expression of key matrix molecules of the cartilage encoded by aggrecan (ACAN) and type II collagen COL2A1, and by downregulating the tissue inhibitors of the matrix metalloproteinase-1 (TIMP1) (Siengdee et al, 2017). Fluoroquinolone treatment has also been widely associated with certain side effects, including the development of severe musculoskeletal disorders, for example, tendinitis and tendon ruptures in humans after a 1-week course of ciprofloxacin, 250 mg twice daily (Akali & Niranjan, 2008), cartilage deformities after receiving ofloxacin, 20 mg/kg once daily for 7 consecutive days in 3-month-old male beagle dogs (Yabe et al, 1997), along with the altering of inflammatory mediators and extracellular matrix (ECM) components, as well as the MMP encoding genes in chondrocyte cultures in vitro (Siengdee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%